Pembuatan Website LP Ma'arif Ponorogo Sebagai Media Publikasi Informasi Serta Peningkatan Profesionalisme Lembaga - Nizar Haris Masruri; Mambaul Ngadimah (LPPM Universitas KH. A. Wahab Hasbullah, 2024)
The website is one of the technology platforms that functions as a medium for disseminating information that can be accessed quickly without space and time limitations through the internet network. In its development, the website has penetrated various fields of life, including educational institutions. Websites in educational institutions are utilized effectively and efficiently to widely disseminate educational and institutional information to attract new prospective students who are not physically reached. In Indonesia, there are many educational institutions, including the Ma'arif NU Educational Institution (LP Ma'arif NU) Ponorogo. LP Ma'arif NU Ponorogo has no official website that accommodates information related to institutions, education, and units. Therefore, the purpose of this service is to assist LP Ma'arif NU Ponorogo in optimizing the dissemination of information to the wider community and especially the educational units under its auspices and increasing professionalism as an educational institution by building a website. This service results in the LP Ma'arif NU Ponorogo website with the address https://maarif.nuponorogo.or.id/. The website contains various things, including information about the institution, information related to educational units under its auspices, and other education-related information.